OXIDATIVE AND ANTIOXIDANT STATUS IN DEPRESSIVE DISORDER PATHOLOGY - Marimuthu, Sanggary (E-Jurnal Medika Udayana; vol 2 no 11 (2013):e-jurnal medika udayana)
Depressive disorder is a psychiatric disorder often found lately. Oxidative stress is a mechanism that promotes the occurrence of major depressive disorder . Oxidative stress is defined as an imbalance between oxidants and antioxidants whereby high oxidant content is due to decrease the antioxidant cap city of the system. Objective : The aim of this study is to assess the oxidative and antioxidative status in plasma in patients diagnosed with clinical depression , and to assess whether there is a relationship between oxidative stress and severity of depression . Methods : In this study we gather 50 patients with depression according to the Diagnostic and Statistical Manual of Mental Disorders fourth edition and 20 healthy control subjects . Activity levels of plasma malondialdehyde , superoxide dismutase and glutathione peroxidase were measured in this study to assess the oxidative status and antioxidative defense prior to antidepressant medication . Results : Patients with depression had higher total plasma peroxide and lower plasma antioxidants than controls . Depressed oxidative stress index values patients were significantly higher than controls , and there is a significant positive correlation between the scale and the Hamilton depression Rating Oxidative stress index value . Conclusion : Patients with major depression are exposed to oxidative stress , and oxidative stress index may be useful to reflect the severity of the disease . Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Oxidative stress, antioxidant capacity, depressive disorders.